Optimization of torrefaction temperature on the physical and chemical properties of ironwood (Eusideroxylon zwageri) as an alternative biofuel - Ichwan Noor Ardiyat; Noor Rahman; Jarot Wijayanto; A'yan Sabitah; Ahmad Robittah (University of Muhammadiyah Malang, 2025)
This study aims to investigate the effect of torrefaction temperature on the physical and chemical properties of ironwood (Eusideroxylon zwageri) and to evaluate its potential as an alternative biofuel. Torrefaction was carried out at 200°C, 250°C, and 300°C for 150 minutes under oxygen-limited conditions, and the resulting char, tar, and gas yields were quantified, while chemical changes were analyzed using Fourier Transform Infrared Spectroscopy (FTIR). The results indicate that increasing temperature significantly affects product distribution, with the highest char yield (52%) obtained at 250°C and increased gas formation at 300°C. FTIR analysis revealed a progressive reduction of hydroxyl (O–H) and carbonyl (C=O) functional groups, indicating enhanced deoxygenation and carbonization at higher temperatures. These chemical transformations suggest improved thermal stability and fuel quality of the torrefied ironwood. It can be concluded that Eusideroxylon zwageri has strong potential as a renewable biofuel feedstock, with torrefaction at 250°C being the most suitable condition for solid biofuel production.